2016
DOI: 10.1152/ajpheart.00388.2016
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia and arterial blood pressure control in humans: role of the peripheral vasculature and carotid baroreflex

Abstract: Intermittent hypoxia (IH) occurs in association with obstructive sleep apnea and likely contributes to the pathogenesis of hypertension. The purpose of this study was to examine the putative early adaptations at the level of the peripheral vasculature and carotid baroreflex (CBR) that may promote the development of hypertension. Ten healthy male participants (26 ± 1 yr, BMI = 24 ± 1 kg/m(2)) were exposed to 6 h of IH (1-min cycles of normoxia and hypoxia) and SHAM in a single-blinded, counterbalanced crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…However, DBP and MAP did increase during the latter half of recovery following an air-breathing time-control and therefore, our conclusions are based on the first 30 min of recovery where IHH is the primary contributing factor. Lasting increases in blood pressure have been previously observed following both acute and chronic intermittent hypoxia in healthy individuals (Foster et al 2009;Gilmartin et al 2010;Tremblay et al 2016). Elevated blood pressure following IHH probably depends on sensory and sympathetic LTF through angiotensin-II type-I receptor signalling (Foster et al 2010;Jouett et al 2017).…”
Section: Cardiovascular Response To Intermittent Hypercapnic Hypoxiamentioning
confidence: 89%
“…However, DBP and MAP did increase during the latter half of recovery following an air-breathing time-control and therefore, our conclusions are based on the first 30 min of recovery where IHH is the primary contributing factor. Lasting increases in blood pressure have been previously observed following both acute and chronic intermittent hypoxia in healthy individuals (Foster et al 2009;Gilmartin et al 2010;Tremblay et al 2016). Elevated blood pressure following IHH probably depends on sensory and sympathetic LTF through angiotensin-II type-I receptor signalling (Foster et al 2010;Jouett et al 2017).…”
Section: Cardiovascular Response To Intermittent Hypercapnic Hypoxiamentioning
confidence: 89%
“…Following periods of IH, activation of the angiotensin-II type-I receptor (AT 1 R) (Fletcher et al 1999;Foster et al 2010;Marcus et al 2010;Jouett et al 2016) has been shown to contribute to the increased sympathetic vasomotor outflow and blood pressure observed in both healthy humans (Foster et al 2009(Foster et al , 2010Gilmartin et al 2010;Tremblay et al 2016;Jouett et al 2017) and animal models (Brooks et al 1997;Fletcher, 2000;Marcus et al 2009). This response depends on peripheral chemoreceptor afferent activity (Fletcher et al 1992) and afferent-efferent translation within brainstem centers, the median pre-optic nucleus and the subfornical organs (Saxena et al 2015;Shell et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study using the same experimental IH model and a 14 day exposure, Tamisier et al (2011) found no change in calf reactive hyperaemia following a 5 min occlusion. Likewise, Tremblay et al (2016) found that 6 h of IH (ODI = 30) did not alter human brachial artery endothelial function assessed by flow-mediated dilatation. Consequently, prolonged IH exposure appears to be a prerequisite to induce endothelial dysfunction, whereas shorter duration IH may not impact or may even provide some beneficial effects to endothelial function, at least for the vascular beds examined in these studies.…”
Section: Detrimental Effects Of Intermittent Hypoxiamentioning
confidence: 89%
“…Gilmartin et al (2010) found that 28 days of IH mimicking an ODI of 30 decreased forearm reactive hyperaemia in response to a 15 min ischaemic challenge (forearm occlusion), a response that is believed to be nitric oxide (i.e. Likewise, Tremblay et al (2016) found that 6 h of IH (ODI = 30) did not alter human brachial artery endothelial function assessed by flow-mediated dilatation. Unfortunately, as forearm reactive hyperaemia was not assessed after removal of IH, it is unclear how long this detriment persisted.…”
Section: Detrimental Effects Of Intermittent Hypoxiamentioning
confidence: 99%